An Investigation On Construction Sequence Of An Arch-Shaped Tensegrity Structure - Rosli, Muhammad Nasrul Asraf (Universiti Sains Malaysia, 2019)
The focus of this study is irregular multi-layer arch-shaped prism tensegrity. A 4- layer practical scale arch-shaped tensegrity structure with span of 4m and height of 2m was constructed in order to study the sequence of construction and effect of self-weight on the final configuration. 1.5mm steel wire rope and 38.1 mm aluminum tube were used for tension and compression members, respectively. The study started with formfinding process where a computing tool that uses a linear approach by combining length relationship condition and force balance equation was used. From the form-finding results, force ratios needed to be applied were determined. Based on cable strength data, the level of pre-stressing force to be applied to each cable were then decided. The prestressing forces in the cables were applied during construction through forced elongation achieved by means of turn-buckles. Through the erection of the 4-layer arch-shaped tensegrity model, the construction sequence starting from first layer and proceeding until the final fourth layer was formulated, tested and finally successfully established. It was found that proper temporary support of ends of compression member and sufficient level of pre-stressing force in cable members are crucial to maintain rigidity of the tensegrity structure. Self-weight of the compression members was found to affect the final height as well as the span of the arch-shaped tensegrity structure.